Training and Pruning Florida Peaches, Nectarines, and Plums - Ali Sarkhosh; James Ferguson (EDIS, 2018)
Written for both homeowners and commercial growers, this 5-page publication explains concepts underlying recommended tree training and pruning practices. It is a minor revision written by Ali Sarkhosh and James Ferguson, and published by the Horticultural Sciences Department, September 2018.